2022
DOI: 10.1088/1361-6463/ac9ce6
|View full text |Cite
|
Sign up to set email alerts
|

Significantly suppressing metal particle-induced surface charge accumulation of spacers in DC gas-insulated power transmission lines

Abstract: In this letter, we report functions of surface roughening and fluorination on suppressing linear metal particle-induced spacer surface charge accumulation. An appropriate increase in spacer surface conductivity by short-term fluorination and roughening not only increases the metal particle lifting voltage, but also weakens the particle activation. The spacer surface charge shows reduced charge density in roughened spacer, while fluorination modification significantly suppresses the charge density on the spacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Liu and others set up particle traps near the spacer to form a region of low electric field, which can inhibit the accumulation of particle charges, thereby reducing the kinetic energy of particle motion [17]. Our preliminary research found that slightly increasing the surface conductivity can increase the particle's take-off voltage and inhibit the particle's range of motion [15].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Liu and others set up particle traps near the spacer to form a region of low electric field, which can inhibit the accumulation of particle charges, thereby reducing the kinetic energy of particle motion [17]. Our preliminary research found that slightly increasing the surface conductivity can increase the particle's take-off voltage and inhibit the particle's range of motion [15].…”
Section: Introductionmentioning
confidence: 92%
“…In the previous study, the movement of spherical and linear metal particles on the surface of basin-type spacer through the scaled GIL model were studied. And the surface charge characterization of basintype spacer during the movement of spherical and linear metal particles under DC voltage was revealed by using the dust method [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that these theories can be consistent with experiments under specific circumstances. Therefore, Zhan et al [143] , Liu et al [144,145] , and Li et al [146] have conducted some research on the structural optimization design of the particle collector. They analyzed the capture efficiency of different structure under DC voltage, and appropriately improved the corresponding size parameters.…”
Section: Gρ Amentioning
confidence: 99%
“…Dielectric barrier discharges (DBDs) have attracted considerable attention from both academic and industrial communities due to their versatile applications, such as surface treatment [1,2], high-voltage engineering [3,4], plasmaassisted combustion [5], and plasma-enhanced catalysis [6,7]. Extensive studies have investigated various key parameters, such as excited species [8,9], electric fields [10,11], and electron behavior [12], during the volumetric process of DBDs.…”
Section: Introductionmentioning
confidence: 99%